Peran Protokol Dalam Melayani Pengaduan Jam Masyarakat - M. Rangga, Phillipiana; Mustafa, Intan; Sedu, Viktor Aryestian (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
Protocols play a very important role in managing public complaints, especially in the context of public services. The protocol functions as a systematic guide in handling and responding to complaints submitted by the public. With a clear protocol, the complaint process becomes more efficient and transparent so that it can increase public trust in government agencies or related institutions. In its implementation, the protocol includes several stages starting from receiving complaints, verification, and continuation. Each step has standards and procedures that must be followed to ensure that each complaint is handled fairly and in a timely manner. Through good complaint management, it is hoped that a harmonious relationship can be created between the community and the government, as well as encouraging active community participation in the development process so that there is no miscommunication between government agencies and the community.